Factors that influence parents satisfaction towards Islamic private school case study at Sekolah Menengah Al-Hidayah (SMAH) / Siti Mariam Mat Puat - Mat Puat, Siti Mariam (2011)
The purpose of this study is to determine the factors that influence parents’ satisfaction towards Islamic school at Sekolah Menengah Al-Hidayah (SMAH). Questionnaires are used to collect the data. A total 215 parents was participating in this study and 145 of the questionnaires get respondents feedback.For this study, three aspects have been considered that are Curriculum aspects, school environment and school organizations. This study also assessed the significant difference of demographic profile (income level and education level) to parents’ satisfaction to send their children towards Islamic private school. The study analyzed using SPSS 16.0 for descriptive analysis while AMOS 18.0 was used for Structural Equation Modeling (SEM).The finding of this study indicated that a factor that affecting parents satisfaction to send their children to Islamic private school is School Environment Aspect. The researcher also identified that there is no significant difference of demographic profile (income level and education level) to parents’ satisfaction to send their children to Islamic private school